MASAIL FIQHIYYAH MELETAKKAN MUSHAF DI ATAS PERUT MAYIT YANG BELUM DIMANDIKAN - Anwar Hafidzi; Muhammad Nasrullah (CV. Adiba Aisha Amira, 2022)
This study discusses placing the mushaf on the stomach of a dead person who has not been washed, what is the legal status of doing so and whether people who die are punished for having hadats because obligatory bathing is obligatory. The author discusses this problem because according to the author, placing the mushaf on the stomach of a corpse that has not been washed is an interesting thing to study. What's interesting lies in the legal status if you do this. This study uses a qualitative method, with reference to field data and literature as the material used as the object of research. The author finds that what is the ruling on the person who did it putting the mushaf on the stomach of the deceased who has not been washed, because the person who dies is required to take a mandatory bath as in the hadith narrated by Imam Bukhari and Imam Muslim about the Prophet Muhammad who ordered to bathe his daughter with a certain number. If it is related to other laws, such as the law on touching the Qur'an when in a state of great hadats (a situation where a person is required to take a mandatory bath) then the law is haraam.